Reproductive biology of three medicinal plants - Liza, Shamim Ara; Rahman, Md. Oliur; Uddin, Md. Zashim; Hassan, Md. Abul; Begum, Momtaz (Bangladesh Journal of Plant Taxonomy, 2010)
<span style="font-family: "Times New Roman"; font-size: 9pt; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: "Times New Roman";">This paper presents the flower morphology, pollination mechanisms and seed germination of three indigenous medicinal plants of Bangladesh namely, Asclepias curassavica L., Clerodendrum viscosum Vent. and Scoparia dulcis L. The minimum days taken for seed germination in Asclepias curassavica, Clerodendrum viscosum and Scoparia dulcis are 6, 14 and 9, respectively. Epigeal type of seed germination has been noted in Asclepias curassavica and Scoparia dulcis, whereas hypogeal type of seed germination has been found in Clerodendrum viscosum. Fruit production is highest in Scoparia dulcis among the species studied and a maximum of 304 seeds are produced per fruit in it. Maximum 108 seeds are produced per fruit in Asclepias curassavica. Among the species investigated Asclepias curassavica and Clerodendrum viscosum are cross-pollinated, and Scoparia dulcis is self-pollinated. Butterflies, bees and ants are noted to be the pollinators in Asclepias curassavica and in Clerodendrum viscosum black ants, butterflies and long tongue hawk moths are the pollinators. <span style="font-family: "Times New Roman"; font-size: 9pt; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: "Times New Roman";">Keywords: <span style="font-family: "Times New Roman"; font-size: 9pt; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: "Times New Roman";">Taxonomy; pollination; seed germination; Asclepias curassavica L.; Clerodendrum viscosum Vent.; Scoparia dulcis L. <span style="font-family: "Times New Roman"; font-size: 9pt; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: "Times New Roman";"><span style="font-family: "Times New Roman"; font-size: 9pt; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: "Times New Roman";">DOI: 10.3329/bjpt.v17i1.5391 <span style="font-family: "Times New Roman"; font-size: 9pt; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: "Times New Roman";"><span style="font-family: "Times New Roman"; font-size: 9pt; mso-fareast-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: "Times New Roman";"> Bangladesh J. Plant Taxon. 17(1): 69-78, 2010 (June)